THE “ROUTE OF THE OVAR TILE”: A CONTEXT FOR TRAINING GEOSCIENCES TEACHERS - Rebelo, Dorinda; Pinto, Maria João; Bonito, Jorge; Morgado, Margarida; Marques, Luis; Andrade, António Soares (Sociedade Brasileira de Geologia, 2018)
Urban space is an outside classroom environment recognized by researchers and teachers as a very much appropriate setting for learning. When a cultural dimension is developed at this environment, this may promote curricular content approaches and reinforce the articulation of Science-Technology-Society (STS). This can promote, for example, urban heritage. This teacher education program focus on tiles covering the front wall of the buildings at the town of Ovar, in the northern part of Portugal as the core of the program. The raw materials, manufacture, application, conservation and restoration techniques were part of the project, that has been designed, implemented and assessed. The program emphasized the role played by interdisciplinary in science education, the potential of diversity of learning environments - the classroom, the streets and squares, the visits to companies and to a School of Arts and Crafts - and the information provided by different professionals involved. Twenty-one teachers of Physics/Chemistry and Biology/Geology were selected as the target audience. This presentation intends to discuss the main issues related to design and implementation of this education program. The assessment carried out by the trainees reveals important indicators.
Keywords: Teacher training; Geoscience education; Tile heritage; Interdisciplinary